Who will take our children? : the Story of evacuation in Britain 1939-1945 - Jackson, Carlton 1933-2014 (Routledge Taylor & Francis Group, 2022)
"A revised edition of a book published in 1985 as Who Will Take Our Children: The Story of the Evacuations in Britain, 1939-1945, this book provides the logistics and planning of the British evacuation program, the experiences of child evacuees aboard ships, and the role of the evacuations in helping to bring about the National Health Service"--Provided by publisher